Transient Down-Regulation of Sound-Induced c-Fos Protein Expression in the Inferior Colliculus after Ablation of the Auditory Cortex - Clarkson, Cheryl; Juíz, José M.; Merchán, Miguel A. (Frontiers in Neuroanatomy, 2010)
We tested whether lesions of the excitatory glutamatergic projection from the auditory cortex to the inferior colliculus induce plastic changes in neurons of this nucleus. Changes in neuronal activation in the inferior colliculus deprived unilaterally of the cortico-collicular projection were assessed by quantitative c-Fos immunocytochemistry. Densitometry and stereology measures of sound-induced c-Fos immunoreactivity in the inferior colliculus showed diminished labeling at 1, 15, 90 and 180 days after lesions to the auditory cortex suggesting protein down-regulation, at least up to 15 days post-lesion. Between 15 and 90 days after the lesion, c-Fos labeling recovers, approaching control values at 180 days. Thus, glutamatergic excitation from the cortex maintains sound-induced activity in neurons of the inferior colliculus. Subdivisions of this nucleus receiving a higher density of cortical innervation such as the dorsal cortex showed greater changes in c-Fos immunoreactivity, suggesting that the anatomical strength of the projection correlates with effect strength. Therefore, after damage of the corticofugal projection, neurons of the inferior colliculus down-regulate and further recover sound-induced c-Fos protein expression. This may be part of cellular mechanisms aimed at balancing or adapting neuronal responses to altered synaptic inputs.